2021
DOI: 10.1039/d1cp02264d
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of selective HDAC2 inhibitors for liver cancer treatment: computational insights into the selectivity mechanism through molecular dynamics simulations and QM/MM calculations

Abstract: The rational design of selective histone deacetylase 2 (HDAC2) inhibitors is beneficial for the therapeutic treatment of liver cancer, though HDAC2 is highly homologous to HDAC8, which may lead to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…HDAC2 is an epigenetic regulator that controls global gene expression in cells [ 48 ]. Although we showed that HDAC2 inhibitors obtained good results in inhibiting tumor growth in cell and animal experiments, HDAC2 is highly homologous to HDAC8, which might result in unexpected side effects due to the paninhibition of HDAC [ 49 ]. Similar to the results of DNMT inhibitors (e.g., 5-aza-dC) in clinical trials [ 50 ], HDAC paninhibitors approved by the Food and Drug Administration (FDA) might lead to side effects, including cardiac disturbance (arrhythmias), gastric issues (vomiting), or hematologic imbalance (anemia) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDAC2 is an epigenetic regulator that controls global gene expression in cells [ 48 ]. Although we showed that HDAC2 inhibitors obtained good results in inhibiting tumor growth in cell and animal experiments, HDAC2 is highly homologous to HDAC8, which might result in unexpected side effects due to the paninhibition of HDAC [ 49 ]. Similar to the results of DNMT inhibitors (e.g., 5-aza-dC) in clinical trials [ 50 ], HDAC paninhibitors approved by the Food and Drug Administration (FDA) might lead to side effects, including cardiac disturbance (arrhythmias), gastric issues (vomiting), or hematologic imbalance (anemia) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%